Is it important to analyse serum liver enzymes in patients with established metabolic syndrome? A Pilot study to tie the knot - Maiti, Saumyajit; Kumar, Arun (Asian Journal of Medical Sciences, 2017)
Background: Metabolic Syndrome (MetS) is one of theemerging health problems which is the major area of concern as it is not only a potential risk factor for some many diseases but it also affecting globally. It is a common multi-factorial disorder of metabolic derangements and prominent etiological factors for the development and progression of atherosclerotic vascular disease and type 2 diabetes. The relation between elevated serum gamma-glutamyltranferase and metabolic syndrome, however, have been not well explored in a developing country like India. Aims and Objectives: The current study was designed to estimate the levels of alanine transaminase (ALT), aspartate transaminase (AST), and gamma-glutamyltransferase (GGT) in metabolic syndrome patients with age-sex matched healthy controls. Furthermore the relation of liver function status with the various biochemical parameters of metabolic syndrome was explored. Materials and Methods: In this present only patients of metabolic syndrome were selected based on inclusion and exclusion criteria of selecting cases. All the biochemical parameters were analysed using standard methods. Data collected were analysed using Statistical Package for the Social Sciences (version 20.0). P value (p<0.05) was considered to be significant. Results: Of the 200 cases and controlsselected, the differences in serum GGT (p<0.001) and ALT (p=0.048) were statistically significant. In case of male subjects,study and controls groups were compared only for serum GGT level (p=0.032) and in case of female subjects, studyand controls were compared for serum ALT (p=0.027) and serum GGT level (p<0.001)and the differences were found to be highly significant. When male and female subjects of study group were compared, significant differences were observed in their serum ALT and GGT levels. Conclusion: Patients suspected of metabolic syndrome must also get their liver profile enzymes analysed as liver functionis also affected with metabolic syndrome and it could be an additional risk factor additive of metabolic syndrome. Early detection and management can be preventive and can have a better treatment modalities is managing patients with metabolic syndrome. It not only prevent disease progression but also prevents additional cost burden beard by the patients. Asian Journal of Medical Sciences Vol.8(3) 2017 35-40